2023
DOI: 10.1007/s12640-023-00648-1
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Interactions of Natural and Synthetic Compounds with Key Proteins Involved in Alzheimer’s Disease: Prospects for Designing New Therapeutics Compound

Abstract: Memory impairment is a result of multiple factors including amyloid-beta (Aβ) accumulation. Several receptors are mediated for Aβ transport and signaling. Moreover, blood lipids are involved in Aβ signaling pathway through these receptors. Mediated blood lipid level by statins aims to regulate Aβ signaling cascade. First, the structure of receptors was taken from the RCSB PDB database and prepared with MGLTools and AutoDock tool 4. Second, the ligand was prepared for docking through AutoDock Vina. The binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This effect is speculated to be related to the regulation of Aβ active transport across the BBB [180]. Recent research, based on clustering and pharmacokinetic analysis, has confirmed that quercetin plays a role in the peripheral clearance of Aβ [181]. Moreover, Li M T et al [182] investigated the protective effects of quercetin on HBMECs, focusing on cell vitality, migration, angiogenesis, and apoptosis.…”
Section: Quercetinmentioning
confidence: 99%
“…This effect is speculated to be related to the regulation of Aβ active transport across the BBB [180]. Recent research, based on clustering and pharmacokinetic analysis, has confirmed that quercetin plays a role in the peripheral clearance of Aβ [181]. Moreover, Li M T et al [182] investigated the protective effects of quercetin on HBMECs, focusing on cell vitality, migration, angiogenesis, and apoptosis.…”
Section: Quercetinmentioning
confidence: 99%
“…111 According to the recently reported studies, among the in silico results of FDA-approved drugs, the binding energies of donepezil were reported between -19.71 kcal/mol and -8.4 kcal/mol calculated by using various algorithms such as AutoDock Vina, Glide/ SP/XP, and MOE etc. [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128] Furthermore, docking scores were given as -10.46 kcal/mol and -7.64 kcal/mol for donepezil and rivastigmine, respectively, by using Glide/ SP. 129 In our previously reported study, we calculated induced fit docking (IFD) and quantum polarized ligand docking (QPLD) scores as -12.20 kcal/mol and -9.54 kcal/mol for known inhibitor neostigmine, respectively, against AChE.…”
Section: In Silico Studiesmentioning
confidence: 99%
“…Rosuvastatin reduces microglial load and ,inhibits inflammatory factors, and has a high affinity for binding to proteins such as acetylcholinesterase (AChE) and Aβ ( 12 ). Molecular pharmacokinetics analysis studies show that rosuvastatin has a high affinity for binding to proteins such as AChE and amyloid beta (Aβ), and is involved in the clearance of Aβ ( 12 , 13 ). Hu et al (2020) demonstrated that Rosuvastatin 10mg once daily for 6 months significantly alleviated the cognitive impairment progression and the risks of dementia in older hypertensive patients ( 14 ).…”
Section: Introductionmentioning
confidence: 99%